Peranan Buah Semangka dalam Pembelajaran Volume Bola - Juwita, Hariani; Putri, Ratu Ilma Indra; Somakim, Somakim (Jurnal Elemen, 2015)
The objective of this study was to investigate the role of the context to enable the students to understand the concept of volume of a sphere in class VIII. The context of this research was using a watermelon as teaching aids by using PMRI approach. The method used in this study was design research; the stages were preleminary design, teaching experiment, and retrospective analysis. The results of this study indicated that the role of watermelon as teaching aids supported the students to develop their knowledge about the concept of volume of a sphere, and enhance their understanding about the material so that the learnin becomes more meaningful. In giving the volume of a sphere its better not to be taught the students by giving formula directly, however they were given the opportunity to understand the volume of a sphere with their own concept in real situation. The existence of such a situation, the student will be easier to learn the material volume of a sphere at a higher level.